The advantages and challenges of superconducting magnets in particle therapy. (30th June 2016) - Gerbershagen, Alexander; Calzolaio, Ciro; Meer, David; Sanfilippo, Stéphane; Schippers, Marco
Abstract: This paper provides an overview of the current developments in superconducting magnets for applications in proton and ion therapy. It summarizes the benefits and challenges regarding the utilization of these magnets in accelerating systems (e.g. superconducting cyclotrons) and gantries. The paper also provides examples of currently used superconducting particle therapy systems and proposed designs.